Mounier Kuhn syndrome in adult: a case report - Deka, Nabanita; Hazarika, Manoj; Goswami, Gautam (International Journal of Research in Medical Sciences, 2017)
Mounier-Kuhn syndrome or tracheobronchomegaly is a rare congenital abnormality of the trachea and main bronchi characterized by marked cystic dilatation of the tracheobronchial tree, associated with tracheal diverticulosis, bronchiectasis and recurrent lower respiratory tract infections. We report a case of 22 years adult male with history of recurrent lower respiratory tract infection.